A combination therapy strategy for treating antibiotic resistant biofilm infection using a guanidinium derivative and nanoparticulate Ag(0) derived hybrid gel conjugate. Issue 34 (18th August 2022) - Dey, Ananta; Yadav, Manisha; Kumar, Deepak; Dey, Anik Kumar; Samal, Sweety; Tanwar, Subhash; Sarkar, Debrupa; Pramanik, Sumit Kumar; Chaudhuri, Susmita; Das, Amitava
Abstract : Dispersion of biofilms that protect bacteria and its subsequent killing in the planktonic state are effectively achieved by a guanidinium–Ag(0) nanocomposite. Abstract : Bacteria organized in biofilms show significant tolerance to conventional antibiotics compared to their planktonic counterparts and form the basis for chronic infections. Biofilms are composites of different types of extracellular polymeric substances that help in resisting several host-defense measures, including phagocytosis. These are increasingly being recognized as a passive virulence factor that enables many infectious diseases to proliferate and an essential contributing facet to anti-microbial resistance. Thus, inhibition and dispersion of biofilms are linked to addressing the issues associated with therapeutic challenges imposed by biofilms. This report is to address this complex issue using a self-assembled guanidinium–Ag(0) nanoparticle (AD-L@Ag(0)) hybrid gel composite for executing a combination therapy strategy for six difficult to treat biofilm-forming and multidrug-resistant bacteria. Improved efficacy was achieved primarily through effective biofilm inhibition and dispersion by the cationic guanidinium ion derivative, while Ag(0) contributes to the subsequent bactericidal activity on planktonic bacteria. Minimum Inhibitory Concentration (MIC) of the AD-L@Ag(0) formulation was tested against Acinetobacter baumannii (25 μg mL −1 ), Pseudomonas aeruginosa (0.78 μg mL −1 ), Staphylococcus aureus (0.19 μg mL −1 ), Klebsiella pneumoniae (0.78 μg mL −1 ), Escherichia coli (clinical isolate (6.25 μg mL −1 )), Klebsiella pneumoniae (clinical isolate (50 μg mL −1 )), Shigella flexneri (clinical isolate (0.39 μg mL −1 )) and Streptococcus pneumoniae (6.25 μg mL −1 ). Minimum bactericidal concentration, and MBIC50 and MBIC90 (Minimum Biofilm Inhibitory Concentration at 50% and 90% reduction, respectively) were evaluated for these pathogens. All these results confirmed the efficacy of the formulation AD-L@Ag(0). Minimum Biofilm Eradication Concentration (MBEC) for the respective pathogens was examined by following the exopolysaccharide quantification method to establish its potency in inhibition of biofilm formation, as well as eradication of mature biofilms. These effects were attributed to the bactericidal effect of AD-L@Ag(0) on biofilm mass-associated bacteria. The observed efficacy of this non-cytotoxic therapeutic combination (AD-L@Ag(0)) was found to be better than that reported in the existing literature for treating extremely drug-resistant bacterial strains, as well as for reducing the bacterial infection load at a surgical site in a small animal BALB/c model. Thus, AD-L@Ag(0) could be a promising candidate for anti-microbial coatings on surgical instruments, wound dressing, tissue engineering, and medical implants.